Evaluation of tomato genotypes (Santa Cruz type) during the Winter season, in Araguari, MG, Brazil - Peixoto, José Ricardo (1999)
A field experiment was carried out in the Jordão farm in Araguari, MG, Brazil, during the winter season, to evaluate the agronomic potential of genotypes (Santa Cruz type) of tomato. The experimental design was in randomized blocks with 14 treatments (genotypes) and four replications. The experimental plot was made up of two lines (1.0 m between lines and 0.6 m between plants) with 12 plants each (two plants/pit). Seventeen harvests were made, starting in 8/25/96, and ending in 10/19/96. In general, all genotypes showed high production compared to the Brazilian production average. The genotypes Santa Clara I-5300, Débora Plus, Santa Clara, Santa Clara (Imported) and Santa Clara III showed production higher than 125 tons/ha, indicating that those genotypes can be cultivated in that region, in the winter season. Only two genotypes, Tom-556 and Ângela Gigante I-5100 did not show fruit weight higher than 100 g/fruit. The cultivars Saladinha, Santa Clara (Imported), Concord and Jumbo showed average weight higher than 130 g/fruit, and high percentage of fruits classified as extra AA type; Santa Clara, Santa Clara I-5300, IAC Santa Clara, while Tom-556, Tex-015 and Ângela Gigante I-5100 presented higher number of fruits type A.